Influence of water/powder ratio in the mineral and synthetic casts - Rudys Rodolfo De Jesus Tavarez; Rufino José Klug; Mayana Soares Vieira; Gisele Lima Bezerra; Matheus Coelho Bandeca; Leily Macedo Firoozmand (Universidade Estadual de Campinas, 2010)
Aim: To evaluate the influence of varying the water/powder ratio on the compressive strength of type IV mineral and synthetic casts. Methods: Four commercial brands of type IV mineral and synthetic casts were evaluated: Durone, Herostone, Fuji Rock, and Elite Rock. Ninety-six test samples were prepared from a silicone matrix, according to ADA's standard no. 25. The samples were prepared according to the manufacturer's recommendations with a normal water/powder ratio (n = 12) and with 20% extra water (n = 12), forming the control (A) and experimental (B) subgroups, respectively. Compressive strength tests were performed using a universal testing machine EMIC (DL 2000) with a load cell of 2,000 kgf/cm2 . The obtained data were analyzed statistically using two-way ANOVA and Tukey's test (α=5%). Results: The synthetic Elite Rock cast was statistically different from the one obtained when the portion of water indicated by the manufacturer was used; no significant differences were found in the remaining casts when the proportion of water was increased by 20%. Conclusions: the groups of synthetic and mineral casts differed and the water increase (20%) did not cause significant difference on the compressive strength of the materials.